Innovative Always - Dave, Shruti; PatDela, Rajendra (London : SAGE Publications Ltd, 2017)
Innovative Always (IA) was a small manufacturing unit specializing in producing a unique product, Zen. The unit was run by five partners who had been together in school.Zen was a product used by local colour and chemical manufacturers in their manufacturing process, so IA had a ready market for its product. The total market was estimated to be around 6,000 units p.m. IA, due to its early entry in this industry enjoyed almost 75% of the market share. Zen was manufactured by a simple process of mixing two raw materials XL and ME in an optimum proportion of 6:4 and then converting the mixture into the finished product, Zen. Though there was no loss while mixing, the final process of converting the mixture into Zen resulted in a loss of 10% of the total input. This conversion process required special skills.
Originally published inDave, D., & Patel, R. (2012). Innovative Always. F&A0493. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Innovative Always (AI); Chemical industry -- India -- Case studies; Small business -- India -- Case studies; Raw materials -- India -- Case studies